ANALYSIS OF STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITY IN THE MATH ESSENTIALS AT AN ISLAMIC MIDDLE SCHOOL IN BANDUNG - Muhammad Ari Subhi; Tatang Herman; Darhim Darhim (Prima: Jurnal Pendidikan Matematika, 2023)
Creativity is an important ability for students to have in the 21st century. The ability to think creatively is very important for innovation, developing original ideas, and finding new ways of thinking for students. In the context of mathematics, the mathematical creativity thinking ability to solve mathematical problems related to everyday life is important. However, the results of previous studies revealed that students' mathematical creative thinking abilities were still relatively low. This study aims to analyze the level of students' mathematical creativity thinking ability at an Islamic Middle School in Bandung. The research method used is descriptive-quantitative. The sampling technique used is purposive sampling. The subjects in this study were 17 eighth-grade students at an Islamic Middle School in Bandung. while the data collection techniques used are tests, questionnaires, and interviews. The test consists of four questions on math essentials based on indicators of mathematical creative thinking ability: fluency, flexibility, originality, and elaboration. The questionnaire consists of 15 closed statements based on 5 attitudes related to mathematical creative thinking abilities, namely: curiosity, imaginativeness, liking challenges, courage, and respect. Unstructured interviews were conducted as a validation of the results of the questionnaire. The results showed that the level of students' mathematical creative thinking ability was divided into 29% of students at level 3, 24% of students at level 2, 18% of students at level 1, and 29% of students at level 0.